TIME MANAGEMENT IN THE HOSPITALITY INDUSTRY: THEORETICAL AND PRACTICAL ASPECTS - Huzar, Uliana; Vozna, Liubov (European Science, 2024)
Today, the initial conditions for successful management of hospitality industry establishments are proper organization and rational use of time. The introduction of an effective time management system at hospitality enterprises increases the efficiency an